2023
DOI: 10.1111/rode.13025
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to rural and agricultural development in the digital age

Abstract: This special issue contributes to the development economics literature by highlighting the role of information communication and technologies (ICTs) in supporting rural and agricultural development. It is comprised of nine papers. Key findings from this special issue include: (1) internet use increases rural consumption diversity and agricultural productivity; (2) smartphone use empowers rural women in household decision‐making and off‐farm work participation; (3) smartphone‐based agricultural extension servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The index system for measuring the digital economy usually includes digital infrastructure [ 33 ], industrial digitization [ 48 ], digital industrialization [ 48 ]and digital innovation [ 46 ]. With reference to the literature, the index system for measuring the digital economy is concerned with the following four aspects: digital infrastructure, industrial digitization, digital industrialization and digital innovation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The index system for measuring the digital economy usually includes digital infrastructure [ 33 ], industrial digitization [ 48 ], digital industrialization [ 48 ]and digital innovation [ 46 ]. With reference to the literature, the index system for measuring the digital economy is concerned with the following four aspects: digital infrastructure, industrial digitization, digital industrialization and digital innovation.…”
Section: Methodsmentioning
confidence: 99%
“…Digital economic development tends to be spatially nonlinear [ 32 ]. Wang and Cen (2022) found that the nonlinear characterization of the increasing marginal effect of the digital economy on innovation efficiency [ 33 ]. Digitization and digital economic development have significant impacts on employment, household income, and investment, but these impacts vary across groups and regions due to differences in the availability of digital infrastructure, digital economic activities, levels of economic development, educational attainment and industry and employment structures [ 31 , [34] , [35] , [36] ].…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Nguyen et al (2023) and Zhuo et al (2023) for Vietnam and China reported that internet facilities and smartphone use are positive determinants of agriculture. Simultaneously, Ma, Mckay, et al (2023) supported that Information and Communications Technology (ICT) products are facilitating to improve the agricultural productivity. The convergence of technological improvements and comprehensive digitalization in emerging countries has shown a novel dimension in the global job migration pattern, causing significant demographic changes (Ahmed et al, 2016).…”
Section: Digitalization Environment and Agricultural Productivity Nexusmentioning
confidence: 99%